Uca (Xeruca), a new subgenus for the Taiwanese fiddler crab Uca formosensis Rathbun, 1921 (Crustacea: Decapoda: Ocypodidae), based on morphological and molecular evidence - Shih, Hsi-Te (Zootaxa, 2015)
The fiddler crab Uca formosensis Rathbun, 1921 (Crustacea: Decapoda: Ocypodidae), restricted to the western part of Taiwan and the offshore Penghu (Pescadores) Islands in the Taiwan Strait, has been placed under the subgenus Uca (Gelasimus) Latreille, 1817 (= Uca (Thalassuca) Crane, 1975) based on only less than a dozen specimens, but later suggested under the subgenus Tubuca Bott, 1973 because the similarity of external morphology. A suite of characters of carapace, major cheliped, gastric mill, male first gonopod, and chela handedness, as well as the phylogenic relationships (mitochondrial 16S rDNA and cytochrome oxidase subunit I, and nuclear 28S rDNA), nevertheless support this species belongs to its own subgenus. A new subgenus Uca (Xeruca) subgen. nov. is herein established for U. formosensis.